Emperor Pickletine rides the bus - Angleberger, Tom (Angleberger, Tom. Origami Yoda book., 2014)
In this final book in the series, the seventh graders of McQuarrie Middle School and their Star Wars-inspired Origami finger puppets go on a field trip to Washington, D.C., on what proves to be a very long trip full of shifting alliances, betrayals, carsickness, and sugar rushes.